Emerging context-dependent dynamics in response to distractor and reward-relevant stimuli in primary somatosensory cortex - Cao, Zhixing (Nanyang Technological University, 2024)
Sensory selection, or selectively responding to reward-relevant stimuli and suppressing response to distractor stimuli, is the core of behavioral flexibility, which is essential for survival in the constantly changing world. A common theory of sensory selection is the attenuation of distractor stimuli after processed by primary somatosensory cortex. However, details of sensory selection before processing in primary somatosensory cortex remain unclear. We trained mice to selectively attend to one of two relevant stimulus modalities according to trial blocks they were in. Using electrophysiology during two-modality goal-directed tasks, we found that in response to the same tactile-auditory stimulus compound, the primary somatosensory cortex showed significant difference in local field potentials (LFPs) based on the currently relevant modality. This finding suggests that sensory selection takes place before sensory signals were transmitted to primary somatosensory cortex.